Pengembangan Media Ensiklopedia Potensi Biomassa Dan Serapan Karbon Hutan Mangrove Di Desa Lapandewa Makmur Dan Pemanfaatanya Sebagai Bahan Ajar Biologi - Jumarddin La Fua; Ayuni Ayuni; Hilda Ayu Melvi Amalia; Sry Sukmawaty (Universitas Nusantara PGRI Kediri, 2024)
An encyclopedia is a scholarly work that contains a detailed summary and discussion of materials. This particular encyclopedia integrates images and textual content, and it is intended for use at the high school level (MA/SMA Class X) in the study of Mangrove Forest Ecosystems. This research aims to explore the utilization of encyclopedias in high schools for teaching Mangrove Forest Ecosystem materials, with the objective of enhancing the teaching and learning process and evaluating the suitability of such encyclopedic materials.The research is conducted using a 4-D model, which includes phases of defining, designing, developing, and disseminating. The research findings demonstrate the significant utility of encyclopedias for both teachers and students, particularly in light of their underutilization in schools. The presence of these encyclopedias not only eases the workload of teachers but also enriches the teaching and learning process with up-to-date content. Furthermor, the evaluation of the encyclopedia teaching materials, conducted by subject matter experts and media specialists, deems them 'feasible' with approval rates of 95.83% and 97.91% respectively.